Textile residue-based mycelium biocomposites from Pleurotus ostreatus - Rahul Saini; Guneet Kaur; Satinder Kaur Brar (Mycology)
The research on mycelium-based biocomposites is increasing exponentially, due to their ability to be produced from renewable and sustainable substrates. In this sense, the present investigation explores the ability of Pleurotus ostreatus to grow on textile residues and form mycelium-based biocomposites. The mycelium was able to grow on four types of textile residues including white and coloured cotton and polyester mixtures and acted as a binder between the textile fibres. The growth of fungal mycelium was assessed using Fourier transform infrared spectroscopy to detect the presence of amides and polysaccharides arising from fungal mycelium and scanning electron microscopy, dry weight and water activity. The compressive strength of textile residue-based biocomposite was also measured and it was found to be between 100 and 270 kPa. Overall, a lightweight biocomposite was obtained which could be a potential alternative for polystyrene-based products. These findings show the ability of the fungus to thrive on polyester plastic in textiles and provide an alternative for converting this plastic material into bio-based materials. Additionally, by varying the mycelium growth, the plasticiser and stiffness properties of the resultant biocomposite can be changed. This research paves the way for the efficient conversion of textile waste into biocomposites as alternatives for plastic packaging products.